PWE-053 Biofeedback in patients with ileoanal pouch dysfunction: a specialist centre experience. (8th June 2018) - Segal, Jonathan; Chan, Heyson; Collins, Brigitte; Faiz, Omar; Hart, Professor Ailsa; Clark, Susan
Abstract : Introduction: Restorative proctocolectomy is performed in patients with ulcerative colitis refractory to medical therapy, UC related neoplasia, and in some patients with familial adenomatous polyposis. Incontinence can occur in up to 12%–31% of patients with an ileoanal pouch. Evacuatory difficulty in the absence of mechanical or anatomical abnormality is uncommon and management options are limited. Incontinence and evacuatory disorders associated with the ileoanal pouch can be particularly problematic and difficult to treat using conventional therapies. Biofeedback therapy is a behavioural treatment which is non-invasive and offers a non-surgical approach as an alternative or adjunct for patients with functional bowel disorders. The theoretical basis for biofeedback is 'learning through reinforcement' or 'operant conditioning' Methods: This was a retrospective single centre study. We reviewed the notes of all patients attending for biofeedback at our institution between Jan 2012 and Oct 2017, and identified all those that did so for ileoanal pouch related problems. We recorded patient reported subjective improvements following biofeedback. The validated International Consultation on Incontinence Questionnaire was used to assess improvement in incontinent symptoms and the evacuatory disorder questionnaire was used to assess improvement in evacuatory disorders. Result: Twenty-six patients with ileoanal pouch related problems underwent biofeedback. Based on patients' feedback at next clinical encounter following biofeedback, nine reported much improvement, 11 reported some improvement and six reported no improvement. In the group treated for incontinence, quality of life improved significantly from a median pre-treatment score of 80 to a post-treatment score of 41 (p=0.01) (table 1). Biofeedback reduced pain, bloating, straining and laxative use in patients with evacuatory disorders. Conclusions: Biofeedback is associated with significant improvement in quality of life as well as possible improvements in symptoms related to both incontinence and evacuatory disorders. It is probably an underused service. Further larger prospective studies are required to assess the efficacy of biofeedback in pouch related dysfunction.